Formulation of solution to prevent lysis time erythrocyte and detecting blood type - Ria Amelia; Elfira Maya Sari (Medisains)
Background: In the examination of blood type using the tube method, a test cell containing 5% erythrocytes of the solution volume is required. The blood type test using the tube method is carried out in hospital blood banks and in the educational world during practical activities. The obstacle in making a 5% erythrocyte solution is that erythrocytes are lysed so that it is made every day. In addition, making a 5% erythrocyte solution takes a long time so it is not efficient.